Direito à saúde e física quântica: a nova racionalidade científica e os direitos fundamentais - Schettino, Sther (2019)
Research carried out from studies in the discipline "Research Methodology", of the FDV stricto sensu post-graduation program, when the process of alignment and dialogue between the themes of quantum physics began, the new directions of science, health and the right. After the collection of bibliographical materials and the preparation of three articles on the theme of quantum, the strategy of organizing the dialogue between the new physics and science, health and law was set up. The thesis was based on theoretical bases and concepts based on the Ethics of Liberation, Dussel and the Ethics of Alterity, and quantum was used as a resource for the deconstruction of themes, especially on the themes of ethics and law. A critical, reflexive process was developed that addressed issues such as the integrity of the subject, ethics, otherness, care as pillars for the realization of citizenship, which can not be complete without the effective realization of the fundamental right to health.